Effects of hydrothermal aging on moisture absorption and property prediction of short carbon fiber reinforced polyamide 6 composites. (15th November 2018) - Sang, Lin; Wang, Chuo; Wang, Yingying; Hou, Wenbin
Abstract: The present work focuses on the effects of hydrothermal aging on moisture absorption and mechanical durability of short carbon fiber reinforced polyamide 6 (CF/PA6) composites by immersion in water at 20 °C, 40 °C and 60 °C. Tensile strength, Young's modulus and impact strength of PA6 and CF/PA6 specimens are monitored, and a predictive model based on Arrhenius methodology has been utilized to estimate the retention of tensile strength. By gravimetric experiments, moisture uptake and diffusion coefficients of PA6 and CF/PA6 composites are analyzed by Fickian model, with good exponentially decaying fit with tensile strength. Graphical abstract: Highlights: Predicted low-temperature durability of tensile strength of PA6 and CF/PA6 composites. A developed correlation with moisture uptake to quantify tensile strength. Identified interfacial damage between CF and PA6 under hydrothermal aging.